2020
DOI: 10.1111/jth.15037
|View full text |Cite
|
Sign up to set email alerts
|

Model‐dependent contributions of FXII and FXI to venous thrombosis in mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…Finally, we recognize that the influence of neutrophils in murine models of venous thrombosis is variable. The strongest evidence to date has been observed in the IVC stenosis model, while some models do not demonstrate a significant contribution of leukocytes to venous thrombosis in otherwise healthy animals 22,24,51,64–67 . However, of importance, several studies have now shown that neutrophilia or elevated NET release contribute to the pathogenesis of venous thrombosis in the IVC stasis, jugular vein Rose Bengal, and lung model of spontaneous thrombosis in the presence of solid or blood cancers 47,68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we recognize that the influence of neutrophils in murine models of venous thrombosis is variable. The strongest evidence to date has been observed in the IVC stenosis model, while some models do not demonstrate a significant contribution of leukocytes to venous thrombosis in otherwise healthy animals 22,24,51,64–67 . However, of importance, several studies have now shown that neutrophilia or elevated NET release contribute to the pathogenesis of venous thrombosis in the IVC stasis, jugular vein Rose Bengal, and lung model of spontaneous thrombosis in the presence of solid or blood cancers 47,68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…The abdomen was opened by midline laparotomy and the bowel externalized and wrapped in wetted gauze. The inferior vena cava (IVC) was stenosed as previously described 23 . At 48 h post‐stenosis induction, the IVC was inspected for the presence of thrombus with any resultant thrombus removed from the IVC and weighed using a microbalance.…”
Section: Methodsmentioning
confidence: 99%
“…In FV Leiden carriers, high FXI levels were suggested to contribute to the risk for VTE [52]. Furthermore, animal models al-so suggest that the activation of FXI by FXIIa promotes pathological thrombus formation [53]. FXI inhibition has been proposed as an innovative therapeutic tool to reduce the risk for VTE [54].…”
Section: Factor VII (Fvii) Deficiencymentioning
confidence: 99%